Indonesian Female Migrant Workers and Violent Extremism: Thoughts, Trends and Women’s Empowerment - Tandos, Rosita (Komunitas: International Journal of Indonesian Society and Culture, 2025)
This study aims to examine the level of violent extremism among former Indonesian Female Migrant Domestic Workers (FMDWs) and explore the factors contributing to their vulnerability to radicalization, including ideological influence, social dynamics, and digital exposure. The research involved 100 former Indonesian FMDWs residing in Indramayu District, West Java. Among them, 58 had worked in Middle Eastern countries (Saudi Arabia, UAE, and Qatar) and 42 in Southeast Asia (Taiwan, Hong Kong, Japan, South Korea, and Malaysia). Data were collected using a mixed-method approach, combining closed and open-ended survey questions. Instrument validity was ensured through expert review and preliminary trials. Data were analyzed using descriptive statistics and thematic qualitative analysis to identify patterns of exposure and engagement with extremist narratives. The findings reveal that while most respondents reject violent extremism and terrorist acts, some showed vulnerability due to isolation, unmoderated religious exposure via social media, and limited access to support systems. A small number admitted encountering radical teachings or invitations to join hardline groups. The study highlights the importance of gender-sensitive counter-extremism strategies and emphasizes the critical role of empowering women in preventing violent extremism.